Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1365-2125.1993.tb04158.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of methotrexate and its 7‐hydroxy metabolite in patients with rheumatoid arthritis.

Abstract: 1 The pharmacokinetics of MTX and its 7-hydroxy metabolite (7-OHMTX) were investigated in nine patients with rheumatoid arthritis (RA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 20 publications
(16 reference statements)
5
65
1
2
Order By: Relevance
“…Both of the formulations were well-tolerated by all volunteers in both phases of the study, with no clinical adverse events. All calculated pharmacokinetic parameter values were in good agreement with the previously reported values (32,33). For the bioequivalence evaluation, C max , AUC 0-t , and AUC 0-∞ were considered as primary parameters.…”
Section: Bioequivalence Studysupporting
confidence: 85%
“…Both of the formulations were well-tolerated by all volunteers in both phases of the study, with no clinical adverse events. All calculated pharmacokinetic parameter values were in good agreement with the previously reported values (32,33). For the bioequivalence evaluation, C max , AUC 0-t , and AUC 0-∞ were considered as primary parameters.…”
Section: Bioequivalence Studysupporting
confidence: 85%
“…This therapeutic agent is minimally metabolized to 7-hydroxy MTX in vivo by hepatic aldehyde oxidase (Lui et al, 1985;Nuernberg et al, 1990;Seideman et al, 1993;Chladek et al, 1997Chladek et al, , 1998 but is a substrate for multiple transport proteins. Reduced folate carrier 1 (RFC1, solute carrier 19A1), cloned from humans, murine, and other species, facilitates the absorption from the intestine and distribution in other tissues (Rajgopal et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…1) structurally similar to folic acid, has been used for the treatment of rheumatoid arthritis at low doses (Weinblatt et al, 1985;Schnabel and Gross, 1994). MTX is minimally metabolized to 7-hydroxy MTX in vivo, whereas most MTX is eliminated as intact drug via renal and biliary excretion in humans (Henderson et al, 1965b;Lui et al, 1985;Nuernberg et al, 1990;Seideman et al, 1993;Chladek et al, 1998), and in the preclinical species including mice, rats, dogs, and monkeys (Henderson et al, 1965a;Steinberg et al, 1982;Masuda et al, 1997). In mice and rats, the routes of biliary and renal elimination contribute almost equally to the total body clearance of MTX, but in monkeys and humans, renal elimination is more extensive than biliary excretion (Henderson et al, 1965a,b;Steinberg et al, 1982;Williams and Huang, 1982;Nuernberg et al, 1990;Masuda et al, 1997).…”
Section: Abstract: Dpc 333 [(2r)-2-{(3r)-3-amino-3-[4-(2-methylquinolmentioning
confidence: 99%
See 1 more Smart Citation
“…This was found by measurement of the parent compound or metabolites in the urine of the workers. Pharmacokinetic studies have shown that large amounts of antineoplastic agents administered to patients are excreted unchanged in their urine [1,7,10,21,31]. These levels are much higher than those found in the urine of hospital workers involved in the preparation and administra tion of these agents.…”
Section: Discussionmentioning
confidence: 99%